PHB synthase from Streptomyces aureofaciens NRRL 2209 - Ramachander, TVN; Rawal, SK (FEMS Microbiology Letters, 2005)
An similar to4.9 kb Sau3A I genomic DNA fragment from the Streptomyces aureofaciens NRRL 2209 aiding in the biosynthesis of PHB in recombinant Escherichia coli has been sequenced and analysed for phaC gene. The putative phaC(sa) gene of 2 kb is 79.1% GC rich and encodes a 63.5 kDa protein. It expressed under its own promoter and significant PHA synthase activity was detected in the recombinant E coli. This is the first putative PHA synthase gene reported from a Streptomyces sp. with serine as the active nucleophile in the conserved lipase box. The phaC(sa) was found in close proximity to a regulatory gene, which apparently regulated the phaC expression. (C) 2004 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: PHA synthase; PHB; Streptomyces

Isolation and heterologous expression of PHA synthesising genes from Bacillus thuringiensis R1 - Desetty, Rohini D.; Mahajan, Vineet S.; Khan, Bashir Mohammad; Rawal, Shuban K. (World Journal of Microbiology & Biotechnology, 2008)
The polyhydroxyalkanoate biosynthesis gene locus from Bacillus thuringiensis R1 was isolated, cloned and analyzed at the molecular level. We found that a similar to 5 kb SacI-ClaI digested fragment of genomic DNA from B. thuringiensis R1 encoding the PHA synthesising genes, conferred PHA producing ability to E. coli. The fragment was sequenced and found to be of 4787 bp with five open reading frames. Sequence alignment with closely related species of Bacillus in the existing database revealed that the ORFs correspond to phaP, phaQ, phaR, phaB and phaC genes. However, E. coli harboring phaP, phaQ, phaR, phaB and phaC locus produced very low PHA. Furthermore, complementation of the locus with phaA from Ralstonia eutropha increased the PHA production in the recombinant E. coli from 3.0% to 24% of cell dry mass. The putative promoter regions and ribosome binding sites were identified for each of the gene. Conserved domains for PHA synthase and aceto-acetyl-coA reductase were also identified. We hence conclude that the PHA operon of Bacillus thuringiensis R1 consists of phaP, phaQ, phaR, phaB, phaC and complementation of the same with phaA is accountable for its high PHA production.
Keywords: aceto-acetyl-coA reductase; Bacillus thuringiensis R1; PHA synthase; polyhydroxyalkanoate